2022
DOI: 10.1590/1519-6984.260039
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and enzymatic capabilities of fungi associated with the digestive tract of larval stages of a shredder insect in Cerrado and Amazon Forest, Brazil

Abstract: Tropical biomes such as Brazilian Cerrado and Amazon Forest have a great diversity of fungi and insects. Interactions between these organisms can be beneficial to both partners. In streams, these interactions contribute to litter decomposition. Studying the digestive tract (DT) of shredder insects as a habitat for fungal microorganisms is an opportunity to obtain fungal strains with biotechnological potential, which may help to understand the symbiotic relationships between these organisms in tropical forests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Connected with the feeding aptitude is the isolation of Cladosporium spp. from the gut of larvae of aquatic shredders of the genera Phylloicus (Trichoptera, Calamoceratidae) and Stenochironomus (Diptera, Chironomidae); these strains displayed cellulolytic and xylanolytic properties in laboratory assays, supporting the hypothesis that they might improve the digestibility of leaves by the insects [63,73,150]. Likewise, Cladosporium spp.…”
Section: Other Ecological Relationshipsmentioning
confidence: 64%
“…Connected with the feeding aptitude is the isolation of Cladosporium spp. from the gut of larvae of aquatic shredders of the genera Phylloicus (Trichoptera, Calamoceratidae) and Stenochironomus (Diptera, Chironomidae); these strains displayed cellulolytic and xylanolytic properties in laboratory assays, supporting the hypothesis that they might improve the digestibility of leaves by the insects [63,73,150]. Likewise, Cladosporium spp.…”
Section: Other Ecological Relationshipsmentioning
confidence: 64%
“…Brazil adult [32] H. hempei Mexico cuticle and gut of females [30] Nomia melanderi western USA diseased larva [41] Parastrongylus megistus Brazil digestive tract [42] Pteroptyx bearni Sabah (Malaysia) eggs [43] T. brasiliensis, T. infestans Brazil digestive tract [25] Triplectides sp. Brazil gut [20] unspecified insect Brazil internal mycobiota [19] V Helicoverpa zea Iowa (USA) dead larva and pupa [22] Ostrinia nubilalis Iowa (USA) dead larva [22] P. megistus Brazil digestive tract [42] T. brasiliensis Brazil digestive tract [25] V C. quinquefasciatus Thailand dead adult [40] Diaphania (Margaronia) pyloalis Japan larva [61] Euops lespedezae Japan mycangia [62] F. polyctena Poland workers [55] Halictus rubicundus India frass [63] Lasioglossum zephyrum India dead larvae [63] Lixus impressiventris South Korea dead insect [54] M. domestica Iran adults [64] M. domestica Brazil diseased adult/larva [36] Periplaneta americana Sumatra (Indonesia) adult [65] Table 1. Cont.…”
Section: Aedes Aegyptimentioning
confidence: 99%
“…Several authors have reported the abundance of those genera associated with the DT of insects (Belmont-Montefusco et al, 2020a;Teixeira et al, 2022;Romão et al, 2024). Penicillium and Aspergillus, which had the highest occurrence in the DT of larvae from trunks in Cerrado streams, were also frequent in association with mosquito larvae (Diptera: Culicidae) of several types of breeding grounds in municipalities of the Brazilian Amazon (Pereira et al, 2009).…”
Section: Fungi From the Dt Of Stenochironomus Larvaementioning
confidence: 99%
“…diversity in taxa as well as the low frequencies of fungal species. Teixeira et al (2022), when studying the DT fungal community of aquatic shredder larvae, recorded a high occurrence of singletons, consequently resulting in a high diversity of fungal species. The authors attributed this to factors such as the influence of different environmental conditions, diets of species, and life cycles of the insects.…”
Section: Influence Of the Substrate On Species Distributionmentioning
confidence: 99%